Historical and contemporary views on cholera transmission: are we repeating past discussions? Can lessons learned from cholera be applied to COVID‐19?. Issue 7 (1st March 2021) - Jensen, Peter Kjær Mackie; Grant, Stephen Lawrence; Perner, Mads Linnet; Hossain, Zenat Zebin; Ferdous, Jannatul; Sultana, Rebeca; Almeida, Sara; Phelps, Matthew; Begum, Anowara
Abstract : Cholera, a devastating diarrheal disease that caused several global pandemics in the last centuries, may share some similarities with the new COVID‐19. Cholera has affected many populations in history and still remains a significant burden in developing countries. The main transmission route was thought to be predominantly through contaminated drinking water. However, revisiting the historical data collected during the Copenhagen 1853 cholera outbreak allowed us to re‐evaluate the role of drinking‐water transmission in a city‐wide outbreak and reconsider some critical transmission routes, which have been neglected since the time of John Snow. Recent empirical and cohort data from Bangladesh also strengthened the dynamic potentiality of other transmission routes (food, fomite, fish, flies) for transmitting cholera. Analyzing this particular nature of the cholera disease transmission, this paper will describe how the pattern of transmission routes are similar to COVID‐19 and how the method of revisiting old data can be used for further exploration of new and known diseases.